Substantiation of organizational-pedagogical environment for the development of health protection competence of future engineers-pedagogues in Ukrainian higher educational establishments - Brytan, Iu. A. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the theoretical organizational-pedagogical environment that ensures the effectiveness of the process of the development of health protection competence of international students who come from the countries of Central Asia with the purpose of receiving engineering-pedagogical education in Ukraine. The significance and possibility of the creation of health-protective educational environment are explained basing on the analysis of the experience of different Ukrainian higher educational establishments; the aspects of activities of different participants of the teaching and learning process are determined in the paper. The necessity of raising relevant awareness of higher education teachers in terms of the organization of health protection activities with students taking into account a gender approach and peculiar features of family education in the countries of Central Asia is conditioned by the need of the valeological knowledge of higher education teachers as well as by their need of being acquainted with the education system of the countries of Central Asia, with its characteristics and differences from the Ukrainian education system, with peculiar features and values of family education in these countries, with the place and role of physical and heath protection activities, etc. The importance of developing students’ motivation for the organization and active participation in an informative leisure on the basis of the health protection activities is conditioned by the necessity of students’ conscious need and interest in understanding and acquiring components of health protection competence. The potential of the leisure activity organized on a voluntary basis and ensuring the active role of students in health protection is exposed in the article. The organization of differentiated physical education of international students according to individually developed strategies provides the use of all physical training directions in educational and extra-curricular activities basing on the personality-oriented approach.